Avaliação do potencial adsortivo de mesocarpo de coco na remoção de corante vermelho reativo 195 em efluentes aquosos - Dantas Filho, Antonio do Nascimento (Universidade Federal Rural do Semi-Árido, 2018)
The textile industry produces dye-rich effluents that when released in hydric bodies hamper the penetration of sunlight, impairing photosynthetic processes. Besides that, dyes have been indicated as potentially toxic substances. In general, the processes of removing of these contaminants have been much studied, with the technique of adsorption standing out for its high efficiency, in addition to operational advantages and the possibility of re-utilizing agricultural waste as adsorbents, benefiting the environment and reducing costs. The present work aims to study the performance of agricultural waste utilized as adsorbents in the bleaching process of synthetic effluent containing 25g/L of reactive red 195 dye. The two best absorbents, untreated coconut mesocarp and coconut mesocarp treated in an alkaline solution, were characterized by granulometry, scanning electron microscopy (SEM), thermogravimetric analysis (TGA), point of zero charge (PZC) and Fourier-transform infrared spectroscopy (FTIR). Next, kinetic and balance study was realized, applying kinetic models and adsorption isotherms. The adsorption tests showed that the untreated mesocarp exhibited removal efficiency of 89,92% in 120 minutes, while the coconut mesocarp treated in an alkaline solution removed 82,88% in 450 minutes for an initial concentration of 25 mg/L, adsorbent dosage of 4g/L and pH 1,0. The maximum adsorption capacity for the untreated coconut mesocarp was 24,04g/g of adsorbent, and for the coconut mesocarp treated in an alkaline solution was of 22,89g/g of adsorbent at 30°C. The kinetic study showed that the data was better adjusted by an Elovich equation, indicating slow chemiosorption. For both adsorbents, the experimental balance results were better described by the Freundlich isotherm, registering better performance by the untreated coconut mesocarp in all the compared temperatures. The thermodynamic study exhibited that the adsorption process is exothermic and spontaneous for all the temperatures evaluated for the untreated coconut mesocarp, however, spontaneity was observed only at the 30°C temperature for the coconut mesocarp treated in an alkaline solution. The conclusion drawn from the results is that the bioadsorbent that was studied is an alternative for dye removal, even if not submitted to previous chemical treatment
Keywords: Adsorção; Mesocarpo de Coco; Corante; Adsorption; Coconut mesocarp; Dye; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA